Quantification of Remimazolam Besylate (CNS7056B) and Its Metabolite (CNS7054X) by LC-MS/MS in Human Plasma Using Midazolam-d4 Maleate as Internal Standard - Schmidt, Stefanie; Krajinovic, Ljubica; Mertens, Christian; Schramm, Lisa; Schüttler, Jürgen; Fechner, Jörg (Journal of Chromatographic Science, 2022)
A new assay was developed to measure the concentration of remimazolam besylate (CNS7056B) and its major carboxylic acid metabolite (CNS7054X) in human plasma. For this new assay method, midazolam-d4 maleate was used as an internal standard. After setting up a previously described assay method, using CNS7056-d4 and CNS7054-d4 as internal standards, analytical results of both methods were compared. For the new analytical method, ultra-high-performance liquid chromatography (UHPLC) with tandem mass spectrometry was applied. A purification method, using solid phase extraction, was developed and validated. The chromatographic separation of the analytes was achieved with a mobile phase gradient using a Water Acquity (TM) UHPLC-System. The Kinetex (TM) biphenyl 50 x 2.1 mm UHPLC column was used with a particle diameter of 1.7 mu m (Phenomenex, Germany). A measuring range of 0.6-2,000 ng/mL for CNS7056B and of 6-20,000 ng/mL for CNS7054X could be achieved with this new assay. The lower limit of quantification was 0.6 ng/mL for CNS7056B and 6 ng/mL for CNS7054X. The assay was validated according to US Food and Drug Administration guidelines. The new method showed an accuracy of 96.9-110.4% and a precision of 2.1-6.7% for both analytes.
CRIS-Team WoS Importer:2022-12-23